Wabah Penyakit Ingusan (Malignant Catarrhal Fever) pada Sapi Bali di Pulau Lombok, Nusa Tenggara Barat, Indonesia (OUTBREAK OF MALIGNANT CATARRHAL FEVER IN BALI CATTLE IN LOMBOK ISLAND, WEST NUSA TENGGARA, INDONESIA) - Wiyono, Agus; Damayanti, Rini (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Malignant catarrhal fever is a fatal disease in Bali cattle caused by Ovine Herpesvirus-2 (OvHV-2) carried by sheep. The virus has not been isolated and the vaccine is not available yet. Diagnosis in the field is observed  by clinical and epidemiological changes confirmed by histopathology and antigen detection by nested polymerase chain reaction (PCR). The purpose of this paper is to provide clinical, pathological and epidemiological features as well as the results of nested PCR examination of MCF outbreaks in Bali cattle that occurred in Lombok island, West Nusa Tenggara. During January to September 2016, 20 out of 231 cattle were  dead and 16 of them had depression, fever, corneal opacity, hypersalivation, purulent nasal discharges and superficial lymph nodes enlargement. There were 10 lambing sheep with the cage were located between 50 to 200 m with the cattle barn which was separated by a barrier wall. Gross lesions were characterized by diffuse hemorrhage in tracheal mucosa, epicard, abomasum, small intestine and urinary bladder and enlargement of superficial lymph nodes.  Microscopiccally, pathognomonic lesions namely necrotizing vasculitis was found in the brain, trachea, cornea, lung, heart, liver, kidney and urinary bladder. Using nested PCR, OvHV-2 virus was detected in peripheral blood leucocytes/PBL in two cattle surviving from MCF  and in ocular, nasal and vaginal swab from ten adult sheep. Clinical, pathological, epidemiological and molecular examinations indicate that 16 cattle were confirmed having MCF transmitted from infected adult sheep grazing and the viruses were spread by  the lambing sheep kept closely to the cattle barn.